تكنولوجيا المعلومات و علاقتها بادارة الموارد البشرية دراسة ميدانية في مؤسسة اتصالات الجزائر بالأغواط - أحمد شخمة; عمر بلي; هند معمري (My University, 2023)
This study aimed to find out the nature of the relationship between information technology and human resource management, and the main question of the study was: What is the nature of the relationship between the use of information technology and human resource management? In our study, we used the descriptive approach, adopting interview and observation as a method for analyzing and extracting answers to questions. The researcher reached the following results that there is a relationship between information technology and human resource management. • We also reached through interviews a very important conclusion that the use of computers in the training process helped in developing the skills of workers within the institution, and this reflects the role of the computer in that. • The results varied on how the training process is evaluated by the computer, and we concluded that it is done by the computer and how to use it, as well as how to search and extract the results through it. •Because of the computer, the way of work changed after using it in the formation process, and this is what the respondents agreed upon, so that they stated that it shortens the time and provides the results quickly. • We found through interviews that the institution conducts employment interviews, so that they conduct interviews to test workers and discuss the information collected about these people as well to accommodate the tribal gains gained. • The new technology contributed wonderfully to the announcement of jobs and their delivery more closely through the Internet and social networking sites, this is agreed upon by the respondents. • Information and communication technology in directing human resources has become a significant contribution as it helps us in the development of enterprise services. It also contributes to creating a competitive advantage and helps develop its jobs and raise the performance of employees. Information technology has improved internal and external communication, improving work productivity through speed. • Human resources within the organization is an important element accurate, adequate and good. In conclusion, we concluded that the use of ICT has a positive impact on human resources management.